Prospects for engineering HIV-specific antibodies for enhanced effector function and half-life. Issue 3 (May 2015) - Boesch, Austin W.; Alter, Galit; Ackerman, Margaret E.
<x xml:space="preserve">Abstract</x> Purpose of review A wealth of recent animal model data suggests that as exciting possibilities for the use of antibodies in passive immunotherapy strategies continue to develop, it will be important to broadly consider how antibodies achieve anti-HIV-1 effect in vivo. Recent findings Beyond neutralization breadth and potency, substantial evidence from natural infection, vaccination, and studies in animal models points to a critical role for antibody Fc receptor (FcR) engagement in reducing risk of infection, decreasing postinfection viremia, and delaying viral rebound. Supporting these findings in the setting of HIV, the clinical maturation of recombinant antibody therapeutics has reinforced the importance of Fc-driven activity in vivo across many disease settings, as well as opportunely resulted in the development and exploration of a number of engineered Fc sequence and glycosylation variants that possess differential binding to FcRs. Exploiting these variants as tools, the individual and concerted effects of antibody effector functions such as antibody-dependent cellular cytotoxicity, antibody-dependent cell-mediated virus inhibition, phagocytosis, complement-dependent cytotoxicity, antibody half-life, and compartmentalization are now being explored. As exciting molecular therapies are advanced, these studies promise to provide insight into optimal in-vivo antibody activity profiles. Summary Careful consideration of recent progress in understanding protective antibody activities in vivo can point toward how tailoring antibody activity via Fc domain modification may enable optimization of HIV prevention and eradication strategies.